Lukisan Pemandangan: Teknik Spon Dalam Karya Seni Lukis Jelekong - Shopia Himatul Alya (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2021)
Nature is a theme that is always present in the development of art in the world, both Western and Asian arts, such as China and Indonesia. The visualization can be a literal or abstract representation. Nature can be an additional element to a painting to convey depth, or perspective. However, the depiction of nature in a painting can also be the main focus of a work of art. In Indonesia itself, there is an Art Village, precisely Jelekong Art Village, where hundreds of people work as painters and some have made nature the main focus of their work. The uniqueness of the Jelekong painter's work lies in the method used and the materials used. So that the authors are interested in further researching the uniqueness of this Jelekong technique. The purpose of this research is to examine the comparison of natural visualization techniques and aspects of Jelekong painting which represent nature in terms of methods and materials. The samples in this study were paintings by Jelekong artists and Western artists. The qualitative descriptive method is considered the most appropriate for analyzing Jelekong painting. The result of this research is that the superiority of the art technique of Ugong painting is the sponge technique created by one of its residents. This technique can create shadow, middle tone, and highlight in a painting. Jelekong's paintings can become the identity of the community in cultivating the local potential of the region